VOCEDplus and Open Access : an ideal relationship - Gamlin, Tracy [Verfasser] (My University, 2022)
Gamlin from the National Centre for Vocational Education Research (NCVER) describes the development of the fulltext database VOCEDplus with its advantages for researchers in Australia and the Asian Pacific area. The repository contains a lot of open access available scientific materials of vocation educational and training. (BIBB-Doku)
Keywords: I 2.3.5 Australien, Ozeanien; 370; 300; Open Access; Berufsbildung; Berufsbildungsforschung; Historische Entwicklung; Elektronisches Publizieren; Fachliteratur; Finanzierung; Australien